TANTANGAN DAN PELUANG MANAJEMEN PARIWISATA HIJAU: STUDI KASUS PADA SALAH SATU EKOWISATA DI BANGLI, TABANAN, DAN JEMBRANA PADA PROVINSI BALI - Ni Wayan Anggreni; I Made Artayasa; I Wayan Sukita (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
This study explores the challenges and opportunities of green tourism management through case studies of several ecotourism destinations in Bali, namely Penglipuran Tourism Village, Wanasari Mangrove Ecotourism in Tuban, and Bali Barat National Park. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the main challenges in implementing green tourism in Bali include low environmental awareness among communities and tourists, limited competent human resources, inadequate eco-friendly infrastructure, and inconsistent policies and supervision. Structural issues such as economic inequality, cultural commodification, and environmental degradation further complicate sustainable management efforts. Nevertheless, the study identifies several strategic opportunities for developing green tourism in Bali, including the growing global trend toward sustainable tourism, the strengthening of community-based tourism villages, the use of digital technology for promotion and environmental monitoring, and multi-stakeholder collaboration involving the government, local communities, academics, and private sectors. In addition, government policies aligned with the Sustainable Development Goals (SDGs) and green certification programs provide greater access to funding and international recognition for environmentally responsible tourism practices. Overall, this study concludes that the success of green tourism management in Bali depends on cross-sectoral commitment, local community capacity building, and consistent sustainable policy implementation. The findings are expected to serve as practical recommendations for local governments, tourism practitioners, and community stakeholders in developing competitive yet environmentally responsible tourism destinations.